Meaning of Care for Students and Teachers from the Faculty of the Nursing Program at the University Francisco de Paula Santander - González Escobar, Dianne Sofía; Docente Facultad Ciencias de la Salud. Universidad Francisco de Paula Santander (Pontificia Universidad Javeriana - Facultad de Enfermería, 2014)
Objective: This study aimed to describe the meaning of care for students and teachersof the nursing program in the second half of 2011.Methods: descriptive exploratoryresearch with a quantitative approach, performed in a sample of 258 studentsand 29 teachers. To collect information it was used the Assessment Scale for CareMeaning, in Spanish: Escala de Evaluación Del Significado Del Cuidar (EESC, forits intials in spanish), ordinal Likert scale with 45 items divided into five categories:Human characteristic, moral imperative, affection, interpersonal relationship andtherapeutic intervention. The statistical analysis of data was based on the calculationof descriptive measures and non-parametric tests such as the Kruskal-Wallistest (H statistic), Kendall's coefficient of concordance and Wilcoxon test, all under asignificance level equal to 0.05. Results: In the overall performance of students andteachers, the category with the highest average score was care as therapeutic intervention,while the category with the lowest score was the care and affection. However,perception of care is different between students and teachers; statistically significantdifferences between categories were identified: human characteristic, affection andtherapeutic intervention, and it was found that the perception of care regarding thesecategories is higher in teachers. Conclusion: We found no consensus when it comesto caring; there are different perceptions of care that exist simultaneously and arenot exclusive. These ways of perceiving the care influence the conceptualization andpractice of nursing.